Cultural factors and design elements in Iranian product design - Abedini, Ahmad (2017)
Traditional products of Iran were created based on the cultural needs as well as functional needs and they are created based on people’s beliefs and customs. Neglecting the cultural needs could raise some anomalies in culture of the society. Traditional products cannot be redesigned unless understanding about the cultural factors that cause these products to be reappeared can be examined. As the nation is progressive in developing facilities for the society in Iran with the increase of global products in current market, traditional products which have strong values for people are facing new challenges. People lives in local with local culture and values which have made their lifestyle during centuries. The adaptation on usage of new the products as well as global products have provided challenges and difficulties for people who are having strong traditional cultural influences beliefs in Iran. People are different in their cognition, perceptions, values due to different cultures and different perception, and different products that will be produced. Iranian government desires to reserve the cultural heritage of Iran society through preserving traditional products with planning for cultural design policy. The new product can be developed based on the integration of understanding between designers, culture and users. In order to hold a place in the globalized market, one needs to fully understand the characteristics of regional culture within the world culture diversity. There is a lack of appropriate methods and in-depth research to support designers for integrating culture into product design especially in Iran. This study aimed to develop a framework to guide designers in designing new product based on cultural factors for Iranian people. This research identified a gap in the established body of knowledge within the early stage and moved on to consider the role of the designer in new product development which concern about cultural factors. Through the first stage, the researcher wanted to complete his perception about cultural factors that influenced creating a particular traditional product during centuries and to study how these can contribute to designer practices. In this study, the qualitative method was used to gain a detailed understanding of the problems and the issues to the related field. The qualitative research is suitable for the study of the social relations. The interview has been conducted to identify the traditional products and essential cultural factors that provide opportunity to be investigated. In the next stage, the researcher explored the design elements that has the abilities to represent the cultural factors, which were obtained through the interview with users in their current lifestyle. Sixteen “Cultural Factors” have been identified through interview with users which contributed to production which proves “Design Elements” have various effects in representing the cultural factors. This research has developed a framework to guide designers in redesigning traditional products, which can be more relevant to the Iranian culture. This work explained how designers could understand the cultural factors and then develop a methodology with design elements for designers to represent those cultural factors to be more compatible for current market in Iran.